Exploration of patients’ and health care professionals’ perspectives of kidney failure risk and shared decision-making in the context of MULTIPle lOng-term condItions aNd frailTy (MULTIPOINT): a qualitative interview and focus group study - Heather Walker; Michael K. Sullivan; Bhautesh Dinesh Jani; Patrick B. Mark; Katie I. Gallacher (BMC Medicine, 2026)
Abstract Background People living with chronic kidney disease (CKD) frequently experience multiple long-term conditions (multimorbidity) and/or frailty. This population is under-researched and shared decision-making in this context is challenging. Clinical guidelines recommend the kidney failure risk equation (KFRE) is used to guide CKD care and referral. This study aims to explore patients’ and healthcare professionals’ (HCPs) perspectives on CKD, including kidney failure risk, and shared decision-making in multimorbidity and/or frailty. A secondary aim is to examine perceptions of KFRE, as a guideline-recommended prognostic tool, in these populations. Methods Semi-structured interviews with patients and focus groups for HCPs from primary and secondary care settings in Glasgow, United Kingdom were conducted March 2024-July 2025. Using a theory-informed abductive approach, data were analysed according to Normalisation Process Theory. Results Thirty-one patients (aged 46–94 years old; 3–10 long-term health conditions; clinical frailty scale of 1–7) and nineteen HCPs participated. Five interconnected factors shaped understanding of CKD, kidney failure risk and shared decision-making, each experienced differently by patients and HCPs: (1) Variable knowledge of CKD, with many patients unaware of their diagnosis and HCPs recognising challenges within time-pressured consultations or with competing priorities; (2) Workload and burden of managing CKD within multimorbidity, including cognitive, practical and emotional demands for patients and competing priorities and complexity for HCPs; (3) Relationships and interactions, where trust and continuity facilitated shared decision-making; (4) Context and priorities, including prioritisation of CKD by patients and HCPs; and (5) Pervasive uncertainty around prognosis, symptom attribution and when to discuss kidney failure risk. KFRE was unknown to patients and most primary care HCPs, secondary care HCPs had greater awareness but expressed mixed views on its application. Conclusions CKD was often not a priority for patients or HCPs, compared to other conditions. Many patients wanted to better understand CKD and kidney failure risk alongside other conditions. Trusting relationships, continuity of care and individual priorities were central to shared decision-making, but frequently undermined by system pressures. Methods of communicating kidney failure risk and uncertainty require further research. Findings provide insights for embedding CKD and kidney failure risk understanding into the care of individuals with multimorbidity or frailty. Trial registration Ethical approval granted in August 2023 by the NHS Health Research Authority following a favourable opinion from the West of Scotland Research Ethics Committee (REC) 3 (IRAS ID: 325848, REC reference: 23WS/0119, Protocol number GN22RE559).